Karakteristik Fisikokimia Ekstrak Kulit Nanas - Nirwana, Fricella Mayanggita; Putri, Selly Harnesa; Suparno, Desy Nurliasari (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2025)
Pineapple is one of the tropical fruits whose production is quite high in Indonesia. Pineapple peel waste is still not widely utilized, even though it contains active compounds that can be obtained through the extraction process. This study aims to determine the physical and chemical characteristics of the extracted pineapple peel. This study's extraction technique is maceration using a 90% ethanol solvent with two variations of maceration length, namely 1 day and 5 days. Rotary vacuum evaporators are used to evaporate the extraction results to create a more concentrated extract. Furthermore, the chemical properties of the extracts were tested through phytochemical screening and testing of extract characteristics including pH value, density, refractive index, and total soluble solids (TPT). The analysis showed that in 1-day maceration, the extract yield was 15.31% with a residual solvent content of 0.92%, while in 5-day maceration, the yield was 21.07% with a residual solvent content of 0.93%. The results of phytochemical testing showed that pineapple peel extract positively contained flavonoids, saponins, and tannins. Pineapple peel extract with 1-day maceration has a pH value of 4.32 ± 0.04, density of 1.387 g/ml, refractive index of 1.489, and total soluble solids of 79.25°Brix. While pineapple peel extract with 5 days maceration has a pH value of 4.38 ± 0.02, density 1.412 g/ml, refractive index 1.494, and total soluble solids 81°Brix. It can be concluded that the difference in maceration duration has a significant effect on the yield and total dissolved solids of the pineapple peel extract.